The maize coleoptiles do not perform typical C4 photosynthesis: investigation with special reference to anatomy, photosynthetic property, and gene expression - Fukaya, Yasuko (2012)
Maize (Zea mays L.) is one of the most representative C4 plants. However, several reports have suggested the occurrence of C3 photosynthesis in this C4 plant. We examined the photosynthetic characteristics of the coleoptiles, as well as the first, the second, and the third leaves of maize seedlings at their maturities. All the foliage leaves examined, including the first leaf sheath, exhibited representative Kranz anatomy, low CO2 compensation point, and expression of genes for enzymes involved in the C4-dicarboxylic acid cycle. In contrast, coleoptiles showed no Kranz anatomy and extremely high CO2 compensation point. The expression of C4-specific genes in the coleoptiles was hampered at various levels. These results strongly suggest that the maize coleoptiles do not perform typical C4 photosynthesis.